The Use of Rotational Atherectomy in the Treatment of Coronary Artery Disease – A Review of Efficacy, Safety, and Clinical Indications - Wysieńska, Maria; Jóźwiak, Piotr; Rybak, Adam; Biaduń-Mućko, Weronika; Rogowska-Borettini, Kinga; Romanowska, Aleksandra; Malmur, Paweł Arkadiusz (Journal of Education, Health and Sport, 2026)
Coronary artery disease is a leading cause of death worldwide, and percutaneous coronary intervention (PCI) is a common treatment. The presence of calcified plaques often makes the procedure difficult, as they limit vessel expansion and proper stent placement. To improve outcomes, several plaque modification techniques have been developed. One of the most widely used is rotational atherectomy (RA). This method employs a diamond-coated burr that rotates at high speed, selectively removing hard, calcified tissue while sparing the softer vessel wall. RA is mainly used as a supportive technique to prepare the lesion and enable effective balloon angioplasty and stent implantation.